324 CONTINUITY OF CARE AND USE OF HIGH-RISK PSYCHOACTIVE MEDICATIONS BY PERSONS WITH DEVELOPMENTAL DISABILITIES. Issue 1 (1st January 2007) - Wood, D. L.; Hall, A.; Zhang, J.; Hou, T.
Abstract : Objective: Studies have found that high-risk psychotropic medication combinations are commonly prescribed to the developmentally disabled; however, causal factors for this observed phenomena are poorly understood. Our study explores the relationship between continuity of primary and psychiatric care and the receipt of high-risk psychoactive medications (two antipsychotics concurrently) by persons with MR/DD. Design: Administrative files from Florida's Program for Persons with Disabilities, which contains demographic and clinical information, from years 2000-2004 were used to identify 18, 159 persons living in Florida with developmental disabilities. We merged these files with the Florida Medicaid Claims database for outpatient services and pharmacy claims and identified all primary care and psychiatric care visits over the 2-year prior to starting the high-risk medication regimen. We calculated the Modified Modified Continuity Index (MMCI) separately for primary and psychiatric care visits for 2 consecutive years. We used two-tailed t -tests, unbalanced ANOVA, and multivariable models tests to test the association between receiving prescriptions for high-risk psychoactive medications and demographic and clinical population characteristics and measures of primary care and psychiatric care continuity. Results: Over 10% (10.82%) of the 18, 159 individuals (1, 964 individuals) were on two antipsychotic medications concurrently (high-risk regimen). The use of two antipsychotic medications varied by gender, race, and age, as well as by geographic and clinical characteristics of the population. Multivariate analyses controlling for sociodemographic and clinical characteristics showed that each primary care visit was associated with a 5% decrease, and each psychiatry visit was associated with a 5% increase in the likelihood of being on two antipsychotics. The Continuity Index for psychiatric care was a significant negative predictor of being on two antipsychotic medications. Persons with high continuity (seeing the same psychiatrist across visits) were eight times less likely (12.6% as likely) to be on two antipsychotic medications compared with persons with low continuity (seeing a different psychiatrist at each visit). Conclusion: Our study shows that both primary and specialty care is associated the use of high-risk psychotropic medications for person with developmental disabilities. Continuity in psychiatric care is particularly important in preventing use of high-risk psychotropic medications in the developmentally disabled population.